Partial least square-structural equation modeling on the gender development index in east java - Sarah Permatasari Aritonang; Trianingsih Eni Lestari; Hendro Permadi (Jurnal Mantik, 2023)
National Term Development Plan (RPJMN) 2015-2019 Based on gender considerations, one of the essential considerations in preparing Indonesia's development plan. The global indicator used to measure the achievement of gender findings is found in the Gender Development Index (IPG). The IPG East Java in 2020 is at the upper middle level, but the disparity in human development still occurs at the district/city level. That is why studying the variables that affect the GPA value is necessary. The method used is Partial Least Square-Structural Equation Modeling (PLS-SEM) with bootstrap parameter estimation. The secondary data were obtained from the Central Statistics Agency (BPS) of East Java and SAKERNAS 2020. The results of this study are that all dimensions of GPI, namely Economy, Health, and Education, have a positive and significant impact on GPI. In comparison, the influential but insignificant variables are AHH Male and AHH Female; RLS Male and RLS Female, AHLS Male and AHLS Female. The most significant contribution is RLS Female, and the smallest is AHLS Male